Suppressing fermi acceleration in a driven elliptical billiard - Leonel, Edson D. [UNESP]; Bunimovich, Leonid A. (American Physical Society (APS), 2010)
We study dynamical properties of an ensemble of noninteracting particles in a time-dependent elliptical-like billiard. It was recently shown that for the nondissipative dynamics, the particle experiences unlimited energy growth. Here we show that inelastic collisions suppress Fermi acceleration in a driven elliptical-like billiard. This suppression is yet another indication that Fermi acceleration is not a structurally stable phenomenon. © 2010 The American Physical Society.